Local public financial management - Shah, Anwar (Public sector governance and accountability series., 2007)
Transparent and prudent local financial management has come to be recognized as critical to the integrity of local public sector and to gaining and retaining trust of local residents. Such integrity and trust is sometimes lacking in some local governments in developing countries, especially in the Africa region. This volume attempts to provide practical guidance to local governments interested in establishing sound financial management systems. Leading international experts have contributed to all relevant aspects of local public financial management - cash management, internal controls, accou.